(untitled) (مجلة إحالات, 2026)
The intervention aims to talk about the literature of epidemics and catastrophes throughout the ages and their impact on humans, and how writers portrayed them with their pens. This is what made us stop at the Corona pandemic in the story “Corona Kills Mary” by the Tunisian writer Saleh Mabrouki, wondering about; How did the writer monitor its events, choose its story, and explain its psychological and physical effects on its characters? Let’s be savedUntil the narrative of diseases and epidemics is a tributary of the literature of epidemics and disasters, and it is as old as humanity. Also, the Corona epidemic, as embodied in the story, had a strong impact on all of humanity, changing the face of the world in all aspects.